LC/MS analysis of cardiolipins in substantia nigra and plasma of rotenone-treated rats: Implication for mitochondrial dysfunction in Parkinson's disease - Tyurina, Y. Y.; Polimova, A. M.; Maciel, Elisabete; Tyurin, V. A.; Kapralova, V. I.; Winnica, D. E.; Vikulina, Anna S.; Domingues, M. R. M.; Mccoy, Jennifer L.; Sanders, L. H.; Bayir, H.; Greenamyre, J. T.; et al. (Free Radical Research, 2015)
Exposure to rotenone in vivo results in selective degeneration of dopaminergic neurons and development of neuropathologic features of Parkinson's disease (PD). As rotenone acts as an inhibitor of mitochondrial respiratory complex I, we employed oxidative lipidomics to assess oxidative metabolism of a mitochondria-specific phospholipid, cardiolipin (CL), in substantia nigra (SN) of exposed animals. We found a significant reduction in oxidizable polyunsaturated fatty acid (PUFA)-containing CL molecular species. We further revealed increased contents of mono-oxygenated CL species at late stages of the exposure. Notably, linoleic acid in sn-1 position was the major oxidation substrate yielding its mono-hydroxy- and epoxy-derivatives whereas more readily "oxidizable" fatty acid residues (arachidonic and docosahexaenoic acids) remained non-oxidized. Elevated levels of PUFA CLs were detected in plasma of rats exposed to rotenone. Characterization of oxidatively modified CL molecular species in SN and detection of PUFA-containing CL species in plasma may contribute to better understanding of the PD pathogenesis and lead to the development of new biomarkers of mitochondrial dysfunction associated with this disease.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Cardiolipin; Oxygenated cardiolipin species; Oxygenated linoleic acid; Parkinson's disease